2020
DOI: 10.3389/fendo.2020.00403
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review: Opposing Pathologies in Cancer and Alzheimer's Disease: Does the PI3K/Akt Pathway Provide Clues?

Abstract: This minireview is a brief overview examining the roles of insulin-like growth factors (IGFs) and the PI3K/Akt pathway in two apparently unconnected diseases: Alzheimer's dementia and cancer. For both, increased age is a major risk factor, and, in accord with the global rise in average life expectancy, their prevalence is also increasing. Cancer, however, involves excessive cell proliferation and metastasis, whereas Alzheimer's disease (AD) involves cell death and tissue destruction. The apparent "inverse" nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 127 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…Fatty acids can also supply carbon to the tricarboxylic acid (TCA) cycle to sustain mitochondrial function [ 16 ]. PI3K-AKT signaling is the most well-known mechanism for activating mTORC1 [ 17 ]. Besides, mTORC1 can be activated or inhibited by various signaling pathways directly or indirectly.…”
Section: Cancer Metabolismmentioning
confidence: 99%
“…Fatty acids can also supply carbon to the tricarboxylic acid (TCA) cycle to sustain mitochondrial function [ 16 ]. PI3K-AKT signaling is the most well-known mechanism for activating mTORC1 [ 17 ]. Besides, mTORC1 can be activated or inhibited by various signaling pathways directly or indirectly.…”
Section: Cancer Metabolismmentioning
confidence: 99%
“…Moreover, the PI3K/Akt signalling pathway has been conserved to regulate and maintain appropriate cell growth, survival and metabolism (Barker et al. 2020 ), which is an important signalling pathway of insulin action and related to NAFLD progression (Zeng et al. 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway is indispensable for cell differentiation, and it has been evolutionarily conserved to maintain appropriate cell growth, survival, and metabolism [ 42 ]. IRS-1 is one of the central mediators in transmitting signals from IGF-IR receptors via the PI3K/AKT pathway and it is commonly overexpressed in cancer [ 43 ]. Meanwhile, Kathryn E et al reported that inhibition of mTOR in tumors caused activation of Akt kinase which is associated with induction of IRS-1 and was prevented by IGF-IR inhibition [ 44 ].…”
Section: Discussionmentioning
confidence: 99%